2005
DOI: 10.1111/j.0022-202x.2005.23914.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Natural Killer Lymphocytes Are Potential Cytotoxic Effectors Against Autologous Malignant Cells in Sezary Syndrome Patients

Abstract: Patients with advanced cutaneous T cell lymphoma (CTCL) exhibit profound defects in cell-mediated immunity. Although it has been suggested that Sezary syndrome (SS) patients have a decreased natural killer (NK) lymphocyte activity, nothing has been reported concerning the sensitivity of Sezary cells to NK lymphocyte-mediated cytotoxicity. Peripheral blood NK cells from healthy donors were tested against Sezary tumoral cell lines as well as against freshly isolated Sezary cells. Further, we studied their abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 39 publications
1
34
0
1
Order By: Relevance
“…However, it remained unclear whether this was due to a decrease of the NK cell numbers, impairment of their cytotoxic function, or both. Recent studies of SS have confirmed a quantitative decrease of NK cells, but also indicate that NK cells are capable of lyzing autologous neoplastic cells as well neoplastic cell lines derived from SS [30,31].…”
Section: Introductionmentioning
confidence: 91%
“…However, it remained unclear whether this was due to a decrease of the NK cell numbers, impairment of their cytotoxic function, or both. Recent studies of SS have confirmed a quantitative decrease of NK cells, but also indicate that NK cells are capable of lyzing autologous neoplastic cells as well neoplastic cell lines derived from SS [30,31].…”
Section: Introductionmentioning
confidence: 91%
“…41 It is also possible that the process of NK-cell recognition of malignant CD4 1 T cells is altered in CTCL patients. Previous studies by Bouaziz et al 15 suggest that NK cells are potentially able to be activated to kill autologous CTCL cells, which suggests that malignant CD4…”
Section: -32mentioning
confidence: 97%
“…Previous groups have reported that NK cells from SS patients are capable of responding to activation ex vivo, indicating the potential for development of immune-based therapeutics. 15 Although MF patients often have a prolonged indolent clinical course of disease that requires localized treatment, there are few effective treatments for the successful management of patients with SS. Because of the lack of success with traditional chemotherapeutic approaches, novel immune-based therapeutics are being developed for use in a multitude of hematologic diseases, including CTCL.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of patients with CTCL, particularly those with advanced stage disease, will ultimately succumb to infectious complications [49][50][51]. Both quantitative and qualitative defects in natural killer (NK) cell [52,53], dendritic cell [54], and T cell-mediated [55][56][57] immunity are observed in CTCL. In addition, CTCL is associated with a significant loss of the T-cell repertoire, analogous to that observed in HIV infection.…”
Section: Immunopathogenesismentioning
confidence: 99%